Candida albicans colonisation, continence status and incontinence‐associated dermatitis in the acute care setting: a pilot study. Issue 3 (1st August 2016) - Campbell, Jill L; Coyer, Fiona M; Mudge, Alison M; Robertson, Ivan M; Osborne, Sonya R
Abstract: Candida albicans is the most prevalent human fungal commensal organism and is reported to be the most frequent aetiological organism responsible for infection associated with incontinence‐associated dermatitis. However, it remains unclear whether incontinence predisposes a patient to increased Candida colonisation or whether incontinence acts as a trigger for Candida infection in those already colonised. The purpose of this observational cross‐sectional study was to estimate colonisation rates of C. albicans in continent, compared to incontinent patients, and patients with incontinence‐associated dermatitis. Data were collected on 81 inpatients of a major Australian hospital and included a pelvic skin inspection and microbiological specimens to detect C. Albicans at hospital admission. The mean age of the sample was 76 years ( SD = 12.22) with 53% being male. Incontinent participants ( n = 53) had a non‐significant trend towards greater Candida colonisation rates at the perianal site (43% versus 28%) χ 2 (1, N = 81) = 4·453, p = ·638 and the inguinal site (24% versus 14%) χ 2 (1, N = 81) = 6·868, p = ·258 compared to continent patients ( n = 28). The incontinent subgroup with incontinence‐associated dermatitis ( n = 22) showed no difference in colonisation rates compared to those without incontinence‐associated dermatitis. Understanding the epidemiology of colonisation may have implications for the prevention of Candida infection in these patients.